2017
DOI: 10.18533/journal.v6i3.1121
|View full text |Cite
|
Sign up to set email alerts
|

Double Life: Music as Work and Serious Leisure

Abstract: Serious leisure (SL) is defined as an intensive, long-term free-time activity which has deep meaning for an individual and generates its own rewards without external incentives. SL has been studied intensively, yet studies on the mutual effects of an individual's work and SL are scanty, especially when music is either the work or the SL. Our research addressed the connection between work and SL with both musicians and non-musicians. The data consisted of nine interviews. Four of the participants were professio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
(21 reference statements)
1
2
0
Order By: Relevance
“…dynamics and unique band identity, 6) teaching and learning, and 7) uses of online platforms and social media. While the first six themes find correspondence with other research as seen in the literature review; other studies have found an additional category of wellness (both mental and physical health), which doesn't feature in this study(Araujo and Rocha 2019, Tong 2019, Humphries 2018, Kuusi and Haukola 2017. Our research identified online platforms and social media which other studies have not.Centrality of music making to membersMembers of the 78 th Fraser Highlanders are, for the most part, younger people with demanding careers and family obligations.…”
supporting
confidence: 80%
“…dynamics and unique band identity, 6) teaching and learning, and 7) uses of online platforms and social media. While the first six themes find correspondence with other research as seen in the literature review; other studies have found an additional category of wellness (both mental and physical health), which doesn't feature in this study(Araujo and Rocha 2019, Tong 2019, Humphries 2018, Kuusi and Haukola 2017. Our research identified online platforms and social media which other studies have not.Centrality of music making to membersMembers of the 78 th Fraser Highlanders are, for the most part, younger people with demanding careers and family obligations.…”
supporting
confidence: 80%
“…As already outlined in the Introduction, core and salient AHC principles include discovering meaning and purpose, developing deep connections with people and nature, moving toward growth and change, maintaining a holistic approach to humanity, and developing creativity (AHC website, [n.d.]; Scholl, 2008). Concerning these specific AHC principles, research demonstrates that serious leisure can result in self-actualization (Heo et al, 2012), personal growth and happiness (Kim et al, 2015), life satisfaction (Kim et al, 2011), increased levels of confidence, skills, and self-esteem (Patterson & Pegg, 2009), friendship and successful aging (Lee et al, 2019), sense of community and belonging (Gallant et al, 2013a), and meaning in life (Konoa et al, 2020;Kuusi & Haukola, 2017: Stebbins, 1998. Research demonstrates that casual leisure can result in balance in life/regeneration in life (MacCosham et al, 2015), relaxation (Patterson, 2004), and interpersonal relationships/friendships (Stebbins, 2020), and project-based leisure can result in meaning and happiness (Bailey & Fernando, 2012).…”
Section: Leisure Within Humanistic Counseling: Developing An Optimal ...mentioning
confidence: 99%
“…In their study, discussions with folk musicians demonstrated the nebulous boundaries between leisure and work; musicians were concurrently engaged in casual leisure, serious leisure, and serious work through cultural production. Kuusi and Haukola (2017) used the serious leisure perspective to examine the experiences of musicians and nonmusicians, exploring the coexistence of work and serious leisure. Vesga Vinchira (2019) used the serious leisure perspective and social practice theory to model the information behavior of fandom as a social practice, observing a number of social and personal factors that influence the information activities and behaviors of fans in their study.…”
Section: Local Music and The Serious Leisure Perspectivementioning
confidence: 99%